N,N `-Bis[(E)-(3-methyl-2-thienyl)methylidene]ethane-1,2-diamine - Prasath, R.; Bhavana, P.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent half-molecules, each being completed by inversion symmetry, comprise the asymmetric unit of the title compound, C14H16N2S2. The major difference between the molecules is found in the central C-C bond [the C-N-C-C torsion angles are 114.66 (18) and 128.94 (18)degrees in the two molecules]. The thiophene and imine groups are almost co-planar in each case [S-C-C-N torsion angles = -6.9 (2) and -3.6 (2)degrees]. In the crystal, the molecules aggregate into supramolecular chains via C-H center dot center dot center dot pi interactions.